Estimating the top-of-atmosphere longwave radiative forcing due to Saharan dust from satellite observations over a west African surface site - Brindley,HE (Atmospheric Science Letters, 2007)
This paper presents a methodology for estimating the longwave top-of-atmosphere direct radiative forcing due to Saharan dust aerosol from satellite observations made by the Spinning Enhanced Visible and InfraRed Imager (SEVIRI) and Geostationary Earth Radiation Budget (GERB) instruments. Narrow-band observations from SEVIRI are used to detect dust presence and quantify its loading, while GERB provides an estimate of the dust impact on the total outgoing longwave radiation. Applying the technique to observations made over the Banizoumbou surface station in Niger through March-June 2006 indicates a midday longwave forcing efficiency of 17 ± 5 W m-2 per unit aerosol optical depth.